5-HT7 receptor modulates GABAergic transmission in the rat dorsal raphe nucleus and controls cortical release of serotonin - Kusek, Magdalena; Sowa, Joanna; Kamińska, Katarzyna; Gołembiowska, Krystyna; Tokarski, Krzysztof; Hess, Grzegorz (Frontiers in Cellular Neuroscience, 2015)
The 5-HT7 receptor is one of the several serotonin (5-HT) receptor subtypes that are expressed in the dorsal raphe nucleus (DRN). Some earlier findings suggested that 5-HT7 receptors in the DRN were localized on GABAergic interneurons modulating the activity of 5-HT projection neurons. The aim of the present study was to find out how the 5-HT7 receptor modulates the GABAergic synaptic input to putative 5-HT DRN neurons, and whether blockade of the 5-HT7 receptor would affect the release of 5-HT in the target structure. Male Wistar rats with microdialysis probes implanted in the prefrontal cortex (PFC) received injections of the 5-HT7 receptor antagonist (2R)-1-[(3-hydroxyphenyl)sulfonyl]-2-[2-(4-methyl-1 piperidinyl)ethyl]pyrrolidine hydrochloride (SB 269970), which induced an increase in the levels of 5-HT and its metabolite, 5-hydroxyindoleacetic acid (5-HIAA) in the PFC. In another set of experiments whole-cell recordings from presumed projection neurons were carried out using DRN slices. SB 269970 application resulted in depolarization and in an increase in the firing frequency of the cells. In order to activate 5-HT7 receptors, 5-carboxamidotryptamine (5-CT) was applied in the presence of N-[2-[4-(2-methoxyphenyl)-1piperazinyl]ethyl]-N-2- pyridinylcyclohexanecarboxamide (WAY100635). Hyperpolarization of cells and a decrease in the firing frequency were observed after activation of the 5-HT7 receptor. Blockade of 5-HT7 receptors caused